ANALISIS PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DIALOG KOPI DI KOTA TIMIKA - ABU BAKAR; ZAINAL ARIFIN; EMILIANA SENTIA LARATMASE; ROSITA MIRYAM MARSYOM; FEBRIANTI TODING BUA (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
The development of coffee shop businesses in Timika City is growing rapidly, making competition between businesses increasingly fierce. This condition forces entrepreneurs to better understand the things that influence a person's decision to buy their products. This study aims to analyze the influence of price, product quality, and service quality on consumer purchasing decisions at Dialog Kopi, Timika City. This research uses a quantitative approach with descriptive methods. The data used is primary data obtained from 28 respondents who have purchased products at Dialog Kopi. The analytical methods used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results showed that individually, price and service quality did not have a significant impact on consumer purchasing decisions. However, product quality has a positive and significant effect. Simultaneously, the three variables, namely price, product quality, and service quality, have a significant effect on consumer purchasing decisions. The value of the coefficient of determination shows that these three variables are able to explain 72.8% of purchasing decisions, while the remaining 27.2% is influenced by other variables not analyzed in this study. The research conclusion shows that product quality is the main factor influencing purchasing decisions at Dialog Kopi, so entrepreneurs need to focus on improving and maintaining product quality in order to attract consumers